Access to drinking safe water and its associated factors among households in East Africa: a mixed effect analysis using 12 East African countries recent national health survey - Bewuketu Terefe; Mahlet Moges Jembere; Nega Tezera Assimamaw (Journal of Health, Population and Nutrition, 2024)
Abstract Background More than half of the population in Sub-Saharan Africa (SSA) faces limited access to safe drinking water. Unimproved water sources can pose risks to the health of entire households, particularly women and children. Despite the fact that East African countries have some of the poorest drinking water infrastructures globally, there is a lack of published data on this issue. Consequently, the objective of this study was to examine access to safe drinking water and its determinants among households in East Africa, utilizing recent nationally representative data. Methods This study analyzed data from recent demographic and health surveys conducted in 12 East African nations between 2011 and 2022. Data were gathered from 204,275 households. A stratified two-stage cluster sampling method was employed, with enumeration areas serving as the main sampling units and households serving as the secondary sampling units. Binary and multiple multilevel logistic regression were used to examine the relevant factors associated with the use of different sources of drinking water in the region. In binary regression and multiple regression, P values of ≤ 0.2 and < 0.05, respectively, were used to determine the statistical significance of variables in the final model. Results Approximately 72.62% (95% CI = 72.43, 72.83) of households have utilized improved sources of drinking water. Household heads aged 25–35 years (AOR = 1.09, 95% CI = 1.04, 1.14), 36–45 years (AOR = 1.09, 95% CI = 1.04, 1.14), and > 45 years (AOR = 1.08, 95% CI = 1.04, 1.14), those with secondary/higher education (AOR = 1.24, 95% CI = 1.20–1.29), and individuals in wealth index categories of poorest (AOR = 0.17, 95% CI = 0.16, 0.18), poorer (AOR = 0.21, 95% CI = 0.19, 0.22), middle (AOR = 0.25, 95% CI = 0.24, 0.27), and richer (AOR = 0.36, 95% CI = 0.34, 0.38) were associated with improved sources of drinking water. Additionally, female household leaders (AOR = 1.23, 95% CI = 1.20, 1.26), > 30 min of time taken to access the water source (AOR = 2.00, 95% CI = 1.95, 2.05), improved toilet facilities (AOR = 2.25, 95% CI = 2.19, 2.31), rural residence (AOR = 0.43, 95% CI = 0.42, 0.45), high community wealth (AOR = 1.31, 95% CI = 1.13–1.51), community media exposure (AOR = 1.32, 95% CI = 1.15, 1.51) were associated with improved sources of drinking water, respectively. Conclusion Approximately three-quarters of the population in East Africa has access to improved drinking water, although the quality of water in the region is still considered poor. It is important for relevant organizations to collaborate in order to improve the quality of drinking water, with special attention given to high-risk groups such as communities with high poverty and low literacy rates, poor households, and rural residents. Strengthening women’s empowerment and increasing mass media exposure can also play a crucial role in accelerating the adoption of improved drinking water sources in East Africa.